Adhesionable flexible GaN-based microLED array film to brain surface for in vivo optogenetic stimulation. (1st April 2022) - Sekiguchi, Hiroto; Matsuhira, Hayate; Kanda, Ryota; Tada, Shuto; Kitade, Taiki; Tsutsumi, Masataka; Nishikawa, Atsushi; Loesing, Alexander; Fukunaga, Izumi; Setogawa, Susumu; Ohkawa, Noriaki
Abstract: A development of a biocompatible, optical stimulation device capable of adhering to the brain surface and activating spatially separated brain regions is necessary for in vivo optogenetic applications. In this study, a hollow structure for isolating the microLED epitaxial layer was fabricated using the anisotropic KOH wet-etching method. Using a thermal release sheet, a method to transfer microLEDs onto a biocompatible parylene film was established without rotation or misalignment of the microLEDs while retaining their characteristics. Accordingly, a flexible microLED array film was fabricated, which adhered to the surface of the brain of a mouse and exhibited blue emission.